1995
DOI: 10.5144/0256-4947.1995.458
|View full text |Cite
|
Sign up to set email alerts
|

Non-Peritonitis Complications of Continuous Ambulatory Peritoneal Dialysis in Saudi Arabia

Abstract: Although peritonitis is the major complication and leading cause of morbidity in patients undergoing continuous ambulatory peritoneal dialysis (CAPD), there are other complications of this long-term renal replacement therapy (RRT) modality. In order to evaluate the non-peritonitis complications, we retrospectively studied 60 new patients who were accepted in our CAPD program over a period of eight years from 1984 to 1993. Out of the 60 patients, 31 were females and 29 were males, with a mean age of 37.0 ± 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…The prevalence of mechanical complications in our study (45.3%) was slightly higher than that of the Moroccan and Pakistani studies, where the prevalence was 37% and 40%, respectively [5] [6]. Open Journal of Nephrology [8] found an even higher prevalence of obstruction (25% of cases).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The prevalence of mechanical complications in our study (45.3%) was slightly higher than that of the Moroccan and Pakistani studies, where the prevalence was 37% and 40%, respectively [5] [6]. Open Journal of Nephrology [8] found an even higher prevalence of obstruction (25% of cases).…”
Section: Discussioncontrasting
confidence: 79%
“…Miftah et al [5], Flayou et al [7], Villemain et Open Journal of Nephrology al. in France [9] and Huraib et al [8] found a higher prevalence at 21.7%, 12.2%, 11.8% and 10%, respectively. In PD this complication generally constitutes the recurrence of a pre-existing hernia and the number increases with age [9] [10].…”
Section: Discussionmentioning
confidence: 99%